Prediction of subclinical left ventricular dysfunction by speckle-tracking echocardiography in patients with anti-neutrophil cytoplasmic antibody--associated vasculitis - İZGİ, TUBA NUR; ATAŞ, HALİL; VELİOĞLU, ARZU; BARUTÇU ATAŞ, DİLEK; ILGIN, CAN; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN; AŞICIOĞLU, EBRU (My University, 2021)
Objectives: This study aims to evaluate left ventricular functions using speckle-tracking echocardiography (STE) in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Patients and methods: Between June 2018 and July 2019, a total of 31 AAV patients (17 males, 14 females; median age: 53 years; range, 47 to 62 years) and 21 healthy controls (11 males, 10 females; median age: 56 years; range, 46 to 60 years) were included in the study. Clinical and biochemical characteristics of all participants were recorded. All participants underwent conventional and two-dimensional STE. The receiver operating characteristic (ROC) curve analysis was performed to determine the cut-off value of serum N-terminal prohormone of brain natriuretic peptide (NT-pro-BNP) that predicted subclinical left ventricular dysfunction. The Spearman correlation analysis was used to determine the correlation between left ventricular global longitudinal strain (LV-GLS) and NT-pro-BNP. Results: The LV-GLS was lower in AAV patients (19.3% vs. 21.7%, respectively; p=0.014). NT-pro-BNP was negatively correlated with LV-GLS (p=0.005, r=0.401). Conclusion: Subclinical left ventricular dysfunction can be detected by STE in patients with AAV who have free of clinically overt cardiovascular disease. The LV-GLS is negatively correlated with serum NT-pro-BNP levels.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Anti-neutrophil cytoplasmic antibody-associated vasculitis; cardiovascular risk; speckle-tracking echocardiography; strain; LEFT ATRIAL VOLUME; INFLAMMATION; ATHEROSCLEROSIS; GRANULOMATOSIS; STRAIN; : Anti-neutrophil cytoplasmic antibody-associated vasculitis; cardiovascular risk; speckle-tracking echocardiography; strain